2022
DOI: 10.3389/fpls.2021.784593
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Quantitative Trait Loci Associated With Partial Resistance to Fusarium Root Rot and Wilt Caused by Fusarium graminearum in Field Pea

Abstract: Fusarium root rot, caused by a complex of Fusarium spp., is a major disease of field pea (Pisum sativum). The development of genetic resistance is the most promising approach to manage the disease, but no pea germplasm has been identified that is completely resistant to root rot. The aim of this study was to detect quantitative trait loci (QTL) conferring partial resistance to root rot and wilting, caused by five fungal isolates representing Fusarium solani, F. avenaceum, F. acuminatum, F. proliferatum, and F.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…The results of the current study validated the stability of genetic resistance in ‘00-2067’. Similar to our previous studies [ 25 , 67 ], significant genotypic effects, a high correlation coefficient within each trait and a negative correlation of root rot severity with vigor and plant height were observed in the RIL population derived from ‘00-2067’ × ‘Carman’. The frequency distribution of the disease severity data for the RIL population suggested that the resistance in ‘00-2067’ was transferred to the progenies in the RIL lines.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The results of the current study validated the stability of genetic resistance in ‘00-2067’. Similar to our previous studies [ 25 , 67 ], significant genotypic effects, a high correlation coefficient within each trait and a negative correlation of root rot severity with vigor and plant height were observed in the RIL population derived from ‘00-2067’ × ‘Carman’. The frequency distribution of the disease severity data for the RIL population suggested that the resistance in ‘00-2067’ was transferred to the progenies in the RIL lines.…”
Section: Discussionsupporting
confidence: 89%
“…The use of partially resistant cultivars is the most effective method to control this disease, particularly given the lack of fully resistant genotypes. The pea cultivar ‘00-2067’ was reported to be partially resistant to infection by A. euteiches under field conditions [ 22 ], and this partial resistance to ARR as well as to Fusarium root rot was further explored in recent studies [ 25 , 67 ]. The most stable and major QTL for resistance to the root rot complex were mapped to two genomic regions on chromosome 4, while minor to moderate QTL were located on chromosomes 5, 6 and 7 [ 19 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disease can reduce the pea crop yield by 30% to 57% [17]. Pea root rot is sometimes referred to as Fusarium root rot as Fusarium species are the predominant pathogens [16,18]). Typical symptoms of root rot are dark-brown lesions on the roots (especially at the base of the roots, close to the soil level); dark spots on the cotyledons, epicotyl, or base of the shoot; and leaf yellowing [19].…”
Section: Introductionmentioning
confidence: 99%
“…2012; Wu et al. 2022), it is not clear how different pea accessions and varieties with pigmented or nonpigmented flowers will respond to a highly aggressive F. avenaceum isolate.…”
Section: Introductionmentioning
confidence: 99%